A Study and Analysis of Sanai's Illustration Techniques With a Mountain in Divan and Hadigheh al-Haqiqa - Ghazi Karbasi, Zahra (2020)
Sanai is considered one of the prominent mystic poets in the field of Persian literature. Relying on various concepts and techniques, he has described his ideas and by simplifying the ambiguous categories, he has increased the power of understanding of his audience. "Mountain" is one of the natural elements that has been repeated many times in Divan and Hadiqah al-Haqiqah. Using literary arrays and various forms of imagination, the poet has created new images that are somehow related to the "mountain". In the present article, based on descriptive method and content analysis technique, Sanai illustration techniques have been explored. The most important findings of the research show that the poet, using literary tools and symbolic capacities of the mountain, has succeeded in representing and explaining the moral and educational, mystical and epistemological concepts, romance and in some cases, descriptive application. And has been praised. Among imaginary forms, simile has the highest frequency and exaggeration has been the most frequent literary array. Using the aesthetic capacities of "Mountain", Sanai, in addition to creating pristine literary images, has made his epistemological ideas attractive and objective.